Pendampingan Pelatihan Perawatan Badan Berkelanjutan Bagi Penerima Manfaat di Panti Pelayanan Sosial PGOT Mardi Utomo Semarang - Nurulisma Saputri; Aulia Romadona; Ani Tias Sinora (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
Skills training organized by the orphanage as an implementation of empowering beneficiaries to express their talents and abilities, gaining knowledge and skills that have been implemented, specifically in the field of body care. Among the existing skills, training in body care, including body massage and body scrubs, was conducted by the Ibu Kartini AKS team. Of the existing skills, training in body care, including body massage and body scrubs, was conducted by the Ibu Kartini AKS team in Semarang for five months last year (2024). Eight sessions were held from November to December 2025, with 10 beneficiaries participating. Community service through Continuous Body Care Training Mentoring for beneficiaries at the Mardi Utomo PGOT Social Home is expected to provide ongoing support in body massage techniques and additional knowledge and skills in the field of body care and spa, particularly foot reflexology. The purpose of this mentoring is to improve the understanding and skills of PGOT beneficiaries. Overall, the mentoring demonstrated that beneficiaries were able to focus on performing body massage according to procedures and focused on learning both soft skills and reflexology foot massage. The average increase in understanding and skills in body care at the end of the activity was significant. Beneficiaries experienced a 70% increase in their performance, as seen in the pre- and post-tests. This was evident in the three stages: planning, implementation, and evaluation. The pre- and post-test results showed an increase in knowledge and skills in body care, including body massage and foot reflexology, across all advanced body care themes.